IoV vertical handoff research based on Bayesian decision - Cun-qun FAN; Shang-guang WANG; Qi-bo SUN; Hua ZOU; Fang-chun YANG (Tongxin xuebao)
Vehicles need vertical handoffs in the heterogeneous wireless network environment of IoV, but current vertical switching technologies generally cannot support vertical handoff among WAVE, WiMAX and 3G cellular. In order to overcome this problem, a vertical handoff method with yesian decision was proposed. Firstly, according to the signal strength, transmission rate, bit error rate, blocking probability, vehicle speed and movement trend, the handoff probability distribution of Multi-condition was established and the handoff prior probability was calculated. Secondly, Bayesian de-cision method was used to obtain the handoff posterior probability and to classify decisions, which made vehicles access the best network. Simulation results show that the proposed method can not only achieve the vertical handoff among WAVE, WiMAX and 3G cellular, but also avoid the ping-pong effect and ensure the network update rate.